Screening of fungal coagulants and their application to reduce turbidity of river water - Jebun, Nesa; Al-Mamun, Abdullah; Alam, Md Zahangir; Ahmad Raus, Raha (2015)
Surface and ground water contain both dissolved and suspended particles. Coagulation and flocculation processes are used to separate the suspended solids portion from the water. Conventionally suspended solids and turbidity are removed from raw water by various chemical coagulants but most of them are costly and non-ecofriendly. Whereas, the bioflocculants are environment friendly and could be used as coagulants. In general, bioflocculants cause aggregation of particles and cells by bridging and charge neutralization. Most solids suspended in water possess a same negative charge since they repel each other when come close together as a result couldn’t settle out of the water. The present study aims to treat a sample of river water and kaolin for the removal of turbidity using fungal coagulants by Jar test. Bioflocculant producing some filamentous fungi were isolated from river water. The strains RWF-01, RWF-02, RWF-03, RWF-04, RWF-05 and RWF-06 showed good flocculating rate. Among them supernatant of RWF-05 and RWF-06 showed turbidity removal (%) at 95% and 75% to kaolin and 23% & 22% to river water respectively. Dried biomass of RWF-03 showed good flocculating rate of 80% after 24h settiling time to kaolin suspension. Result showed the clay particles of river water and koalin has entraped by the fungal supernatant and dried biomass and as a result they reduced the turbidity of river water.